Transformation of Learning in Madrasah: Best Practices in the Implementation of Kurikulum Merdeka at MTsN 2 Bener Meriah - Mukhlis Ismail; Putri Yanti; Ega Gradini; Muhammad Yunus; Fadliadi Ubit (Jumper: Journal of Educational Multidisciplinary Research, 2025)
This study aimed to document and analyze best practices in the implementation of the Kurikulum Merdeka at MTsN 2 Bener Meriah, focusing on initial challenges and adaptive strategies employed. Utilizing a qualitative case study design, the research involved the school principal, 25 teachers, and 88 students through participant observation, in-depth interviews, and document analysis. Data were analyzed using a thematic approach with triangulation from multiple sources. Results indicate that the implementation was effectively supported by community-based training conducted by Balai Diklat Keagamaan Aceh, which enhanced teachers’ understanding and skills. A series of workshops on learning objectives, lesson planning, assessment, and module development contributed to a paradigm shift from teacher-centered to student-centered learning. Classroom implementation, accompanied by collaborative reflection with academic supervisors, improved both the quality of teaching and student engagement by up to 70%. Additionally, P5RA projects, namely, Anti-Bullying Seminar, Pottery Making, and Voice of Democracy, successfully integrated Pancasila and Islamic values into meaningful learning experiences. Key supporting factors included transformative leadership by the school principal and robust teacher collaboration, while challenges such as limited infrastructure and varied teacher readiness were mitigated through resource optimization and peer mentoring. The study concludes that community-based training and collaborative reflection are critical to the successful implementation of the Kurikulum Merdeka and offers important implications for similar strategies in other Islamic education institutions.